Assistance for organic cattle certification for motilango cattle breeders groups, Bogani Nani Wartabone National Park, Gorontalo Province - Bambang Susilo; Hendrix Yulis Setyawan; Aris Subagiyo; Basir Noho; Azwar Lahusin; Irwan Bempah; Wafa Nida Faida Azra; Rizki Putra Samudra; Harki Himawan; Siti Lailatus Sa’adah; Simon Azriel Napitupulu; Rachmad Pratama Fauzi; Mohammad Fatoni Putrafardani; Prayer Immanuel Nicolaus Silaban (Universitas Muhammadiyah Magelang, 2023)
Bogani Nani Wartabone National Park (TNBNW) is a national park located in the Bone Bolango Regency, Gorontalo Province. Within this national park, there is the Pinogu sub-district, which possesses high-potential commodities, namely coffee and cattle. However, access to the sub-district is relatively difficult, resulting in Pinogu not fully utilizing its resources, particularly in the livestock sector. Considering that Pinogu is an organic area, all products originating from Pinogu should adhere to organic standards. To support this assertion, there is a need for organic certification from official institutions. Therefore, assistance was provided to help prepare organic cattle certification for Pinogu livestock groups, enabling them to obtain organic cattle certification from official institutions through outreach, document collection, and interviews. The outcome of this program is the necessary documentation and data required to meet the organic cattle certification requirements.